GD2 redirected CAR T and activated NK-cell-mediated secretion of IFNγ overcomes MYCN-dependent IDO1 inhibition, contributing to neuroblastoma cell immune escape. Issue 3 (18th March 2021) - Caforio, Matteo; Sorino, Cristina; Caruana, Ignazio; Weber, Gerrit; Camera, Antonio; Cifaldi, Loredana; De Angelis, Biagio; Del Bufalo, Francesca; Vitale, Alessia; Goffredo, Bianca Maria; De Vito, Rita; Fruci, Doriana; et al.
Abstract : Immune escape mechanisms employed by neuroblastoma (NB) cells include secretion of immunosuppressive factors disrupting effective antitumor immunity. The use of cellular therapy to treat solid tumors needs to be implemented. Killing activity of anti-GD2 Chimeric Antigen Receptor (CAR) T or natural killer (NK) cells against target NB cells was assessed through coculture experiments and quantified by FACS analysis. ELISA assay was used to quantify interferon-γ (IFNγ) secreted by NK and CAR T cells. Real Time PCR and Western Blot were performed to analyze gene and protein levels modifications. Transcriptional study was performed by chromatin immunoprecipitation and luciferase reporter assays on experiments of mutagenesis on the promoter sequence. NB tissue sample were analyzed by IHC and Real Time PCR to perform correlation study. We demonstrate that Indoleamine-pyrrole 2, 3-dioxygenase1 (IDO1), due to its ability to convert tryptophan into kynurenines, is involved in NB resistance to activity of immune cells. In NB, IDO1 is able to inhibit the anti-tumor effect displayed by of both anti-GD2 CAR (GD2.CAR) T-cell and NK cells, mainly by impairing their IFNγ production. Furthermore, inhibition of MYCN expression in NB results into accumulation of IDO1 and consequently of kynurenines, which negatively affect the immune surveillance. Inverse correlation between IDO1 and MYCN expression has been observed in a wide cohort of NB samples. This finding was supported by the identification of a transcriptional repressive role of MYCN on IDO1 promoter. The evidence of IDO1 involvement in NB immune escape and its ability to impair NK and GD2.CAR T-cell activity contribute to clarify one of the possible mechanisms responsible for the limited efficacy of these immunotherapeutic approaches. A combined therapy of NK or GD2.CAR T-cells with IDO1 inhibitors, a class of compounds already in phase I/II clinical studies, could represent a new and still unexplored strategy capable to improve long-term efficacy of these immunotherapeutic approaches.